STUDY ON THE CHEMICAL INDEX OF ALTERATION OF NEOPROTEROZOIC STRATS IN THE TARIM PLATE AND ITS IMPLICATIONS - Liu B.; Xu B.; He J.Y.; Wei W.; Meng X.Y.; Kou X.W.; Mi H. (My University, 2007)
The method of Chemical Index of Alteration (CIA) is applied to the researches of Neoproterozoic strata in Quruktagh and the discussion of paleoclimate changes. The experimental data show that samples of the Beiyixi Formation are characterized by low CIA value, ranging from 51 to 56, implicating the glacier environment. The CIA values of the samples of the Zhaobishan Formation are about 60, showing a warmer paleoclimate. The CIA values of most samples of the Aletonggol Formation range from 48 to 61 and abruptly rise to 69-71 in the top, showing another cold event during the Altonggol period ended by a warm environment. The CIA values range from 49 to 53 in the following Tereeken Formation, implying the third cold period. The average CIA value of the Zhamoketi, Yukengou and Shuiquan formations is 65, suggesting a warm sedimental condition. The CIA values of the Hankalchough Formation fall to about 56, implicating the forth cold event during the terminal Neoproterozoic. The evidences above show that there were four warm-cold conversions in the Neoproterozoic in Quruktagh, Xinjiang. Among these, the key issue is the cold-warm conversion abruptly happened within the Aletonggol period, which indicates a distinct process from cold to warm and can be regarded as another independent ice age between the Beiyixi and the Tereeken ice ages. This research supports the hypothesis of quartered ice age in the Tarim plate in the Neoproterozoic. By a correlation of the Neoproterozoic ice ages between Tarim and Yangtze plates, the former three of the four ice ages in the Tarim plate can be traced in Yangtze plate.
Keywords: CHEMICAL ALTERATION INDEX; NEOPROTEROZOIC; PALEOCLIMATE; TARIM PLATE; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская